Integrated transcriptomic, untargeted and targeted metabolomic analyses reveal seasonal regulatory mechanisms of vascular cambium activity in woody plants: insights from Schima superba - Wu, Yuanhang; Yan, Qingyu; Zou, Jingjing; Chen, Hongguo; Zhang, Yingting; Xia, Hui (Frontiers in Plant Science, 2026)
IntroductionThe vascular cambium is a pivotal tissue that drives secondary growth in woody plants, directly determining wood structure and properties. Schima superba, a valuable timber species in China, holds considerable ecological and economic importance. However, the seasonal activity of its cambium remains poorly understood.MethodsTo elucidate the underlying molecular and metabolic regulatory mechanisms, we integrated untargeted metabolomics, lignin-targeted metabolomics, and transcriptomic analyses.ResultsUntargeted metabolomic profiling identified 2,178 differentially synthesised metabolites (DSMs), predominantly associated with amino acid metabolism, fatty acid metabolism, phenylpropanoid biosynthesis (PB), and plant hormone signal transduction (PHST). Lignin-targeted metabolomics detected 8 DSMs, most of which initially increased and subsequently declined, peaking in August, with the exception of sinapyl alcohol and L-phenylalanine. Transcriptomic analysis identified 19,609 differentially expressed genes (DEGs), primarily enriched in PB and PHST pathways. Key PB-related structural genes, including SsPAL, SsC4H, Ss4CL, SsCOMT, and SsCAD, exhibited peak expression during the cambial active period, correlating with lignin intermediate accumulation and indicating tight coordination between transcriptional activity and metabolic flux during lignification. PHST-related genes involved in auxin (AUX), cytokinin (CTK), and gibberellin (GA) signalling, such as SsARF, SsSAUR, and SsARR-B, displayed stage-specific expression patterns regulating cambial cell expansion and division. Weighted gene coexpression network analysis (WGCNA) further identified core transcription factors, including SsMYB, SsbHLH, SsWOX, SsGRAS, SsSAUR, and SsNF-YB, as regulators of seasonal cambial activity.DiscussionThese findings provide a comprehensive framework for understanding seasonal cambial activity in S. superba, and offer valuable insights into the regulatory mechanisms of vascular cambium activity in woody plants, thereby supporting targeted wood quality improvement and advancing our understanding of plant developmental biology.